Implikasi Penggunaan Alat Sadap “Zero-Click ” Dalam Penanganan Kasus Cyber Crime - Dewa Gede Ary Krisna; Ida Ayu Putu Widiati; Ni Made Sukaryati Karma (Jurnal Analogi Hukum, 2025)
In Indonesia, technological progress is very rapid, but some people take advantage of this by committing criminal acts. This will have an impact on the protection of personal data. CyberCyber security in the form of wiretapping has a very important role. The formulation of the problem raised is 1) how is the regulation of the use of "zero-clickzero-click" tapping tools in cybercyber crimecrime cases, and 2) how are the implications of the use of "zero-clickzero-click" tapping tools in handling cybercyber crimecrime cases on personal data security? The research conducted is normative juridical, which is a deductive research that begins with analyzing the articles in the governing legislation. The results of the research show that the act of wiretapping is regulated in Article 5 Paragraph (2) and Article 31 Paragraph (3) of the Electronic Information and Transaction Law, there is an expansion of evidence where legally, wiretapping is a legal action. The act of wiretapping is contrary to human rights in the protection of personal data, so the government guarantees data confidentiality for victims which has been regulated in Article 17 of the Minister of Communication and Information Technology Regulation Number: 11/PER/M.KOMINFO/02/2006 relating to Technical Tapping.